Synthesis, Characterization, and Cytotoxic Evaluation of Some Newly Substituted Diazene Candidates - Mohamed El-Naggar; Abdel-Nasser El-Shorbagi; Dina H. Elnaggar; Abd El-Galil E. Amr; Mohamed A. Al-Omar; Elsayed A. Elsayed (Journal of Chemistry)
A series of azocompounds containing methyl salicylate 4a–k and 1-naphthyl moiety 6–8 was synthesized and tested as anticancer agents. Nitrosation of methyl 5-amino-2-hydroxybenzoate or 1-aminonaphthalene by using NaNO2 in the presence of HCl afforded diazonium salt derivatives 2 and 5, which were treated with substituted imino or substituted amino derivatives, to give the corresponding substituted amino-pent-2-en-3-yl-diazenylbenzoate 4a–k or 2-substituted-1-(naphthalen-1-yl)diazene derivatives 6a–h, 7a,b, and 8a,b. All the synthesized compounds were elucidated by elemental analysis and spectroscopic evidence.